Systemic Responses of Multidrug-Resistant Pseudomonas aeruginosa and Acinetobacter baumannii Following Exposure to the Antimicrobial Peptide Cathelicidin-BF Imply Multiple Intracellular Targets - Liu, Cunbao; Shan, Bin; Qi, Jialong; Ma, Yanbing (Frontiers in Cellular and Infection Microbiology, 2017)
Cathelicidin-BF, derived from the banded krait (Bungarus fasciatus), is a typically cationic, amphiphilic and α-helical antimicrobial peptide (AMP) with 30 amino acids that exerts powerful effects on multidrug-resistant (MDR) clinical isolates, including Pseudomonas aeruginosa, Acinetobacter baumannii and Klebsiella pneumoniae, but whether it targets plasma membranes or intracellular targets to kill bacteria is still controversial. In the present study, we demonstrated that the disruption of bacterial membranes with high concentrations of cathelicidin-BF was the cause of bacterial death, as with conventional antibiotics at high concentrations. At lower concentrations, cathelicidin-BF did not cause bacterial plasma membrane disruption, but it was able to cross the membrane and aggregate at the nucleoid regions. Functional proteins of the transcription processes of P. aeruginosa and A. baumannii were affected by sublethal doses of cathelicidin-BF, as demonstrated by comparative proteomics using isobaric tags for relative and absolute quantification and subsequent gene ontology analysis. Analysis using the Kyoto Encyclopedia of Genes and Genomes showed that cathelicidin-BF mainly interferes with metabolic pathways related to amino acid synthesis, metabolism of cofactors and vitamins, metabolism of purine and energy supply, and other processes. Although specific targets of cathelicidin-BF must still be validated, our study offers strong evidence that cathelicidin-BF may act upon intracellular targets to kill superbugs, which may be helpful for further efforts to discover novel antibiotics to fight against them.